A High-Energy Room-Temperature Sodium-Sulfur Battery - Xin, Sen; Yin, Ya-Xia; Guo, Yu-Guo; Wan, Li-Jun (Advanced materials (Weinheim), 2014)
Employing small sulfur molecules as the active cathode component for room‐temperature Na‐S batteries, reveals a novel mechanism that is verified for the batteries' electrochemistry. The sulfur cathode enables a complete two‐electron reaction to form Na2 S, bringing a tripled specific capacity and an increased specific energy compared with traditional high‐temperature Na‐S batteries. At the same time, it offers better cycling stability endowing the batteries with a longer lifespan.